COLLABORATIVE GOVERNANCE AND HUMAN RESOURCES CAPACITY IN CLIMATE CHANGE MITIGATION: STUDY OF NRDC AND THE GOVERNMENT OF INDIA - Heriyanto; Made Marup Wirasenjaya (International Relations Study Program of Universitas Kristen Indonesia (UKI), 2026)
Climate change mitigation in developing countries increasingly demands collaborative governance frameworks that integrate state and non-state actors to build sustainable human resource capacity. This article examines the partnership between the Natural Resources Defense Council (NRDC), an international environmental non-governmental organization, and the Government of India from 2009 to 2016. Drawing on transnationalism theory and Philip Eldridge’s NGO-government partnership framework, this research analyzes how collaborative mechanisms enhance human resource capacity through knowledge transfer, technical assistance, and institutional strengthening. Using qualitative document analysis, the study reveals eight strategic initiatives. Findings demonstrate that the High-Level Partnership, Grassroots Development model enabled NRDC to provide technical expertise while respecting India’s sovereignty, resulting in significant renewable energy expansion (wind: 11 GW to 28 GW; solar: minimal to 9 GW), energy efficiency improvements through the PAT scheme, and enhanced climate policy capacity culminating in India’s Paris Agreement ratification. This collaborative governance approach created synergies by combining NRDC’s international expertise with India’s regulatory authority, contributing to India’s emergence as a global climate leader.